2022
DOI: 10.18860/ling.v16i2.12225
|View full text |Cite
|
Sign up to set email alerts
|

Functioning Discourse Markers to Construct a Social Situation in Speech

Abstract: This study relates the discussion of discourse markers to their functions from a social context. It aims to identify discourse markers and analyze their function to construct a social situation in Steve Jobs’ speech delivered at Stanford Commencement Address. To analyze the data in this study, the researchers used a qualitative descriptive method. This study showed that the dominant discourse markers used were connective, followed by cause result, temporal adverb, and marker of response, respectively, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…Discourse markers are linguistic features that rely on their order and purpose to define segments of spoken language (Schiffrin, 1987). This finding aligns with previous studies that have demonstrated the role of discourse markers as strategic tools for organizing and structuring verbal communication at various levels, including interpersonal, referential, structural, and cognitive (Arya, 2020;Jayantini et al, 2022;Truong, 2022). Additionally, these studies have highlighted the significance of discourse markers in English conversations, facilitating effective communication and conveying the speaker's attitude.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Discourse markers are linguistic features that rely on their order and purpose to define segments of spoken language (Schiffrin, 1987). This finding aligns with previous studies that have demonstrated the role of discourse markers as strategic tools for organizing and structuring verbal communication at various levels, including interpersonal, referential, structural, and cognitive (Arya, 2020;Jayantini et al, 2022;Truong, 2022). Additionally, these studies have highlighted the significance of discourse markers in English conversations, facilitating effective communication and conveying the speaker's attitude.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the current body of research on the relationship between discourse markers and students' speaking skills is primarily focused on the effects of mastering discourse markers on speaking skills without considering the integration of learning media (Arya, 2020;Jayantini et al, 2022;Truong, 2022). The research findings below demonstrate that learning media, specifically scrabble words and flashcards, effectively enhances vocabulary acquisition.…”
Section: Introductionmentioning
confidence: 94%
“…Further, the study highlights a broader issue which is about a substantial number of students show proficiency in using discourse markers compared to those who do not, underscoring a need for targeted educational strategies at MA Negeri 1 Serang. This finding aligns with multiple studies suggesting that understanding and using discourse markers effectively can enhance speaking skills (Arya, 2020;Aşik & Cephe, 2013;Jayantini et al, 2022;Sujarwati, 2017;Truong, 2022). However, it contrasts with research by Khamenei and Faruji (2020), who observed no significant effect of discourse markers on the speaking achievements of EFL students at an intermediate level.…”
Section: Figure 1 Interactive Effects Of Variablessupporting
confidence: 84%
“…Moreover, the existing research on the correlation between discourse markers and students' speaking skills primarily concentrates on the impact of acquiring discourse markers on Fung & Carter, 2007;Jayantini et al, 2022;Sujarwati, 2017;Truong, 2022). The research findings indicate that the use of discourse markers has positively influenced students' oral communication skills.…”
Section: Introductionmentioning
confidence: 93%
“…Successful speakers are those who have the ability to employ whole sentences and ensure coherence in their discourse. Discourse markers (DMs) function as connectors between ideas or topics in a speech to enhance its comprehensibility (Jayantini et al, 2022).…”
Section: Introductionmentioning
confidence: 99%